NILAI EKONOMI SUMBER DAYA HUTAN ALAM SEKUNDER DI KABUPATEN KOTAWARINGIN TIMUR PROVINSI KALIMANTAN TENGAH: R.M. Sukarna, Santosa Yulianto, Reri Yulianti - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTThe rate of forest degradation and deforestation in Central Kalimantan Province between in 1991 to 2001 ± 3.3% peryears, between in 2000 to 2009 ±0,1% per years, between in 2009 to 2013 ±1,2% per years. These conditions havean impact on decreasing of economic value of upstream forestry sector in Indonesia in 2015 is equal to ± 1.5% ofGross Product Domestic. Gross Regional Domestic Product (GRDP) of Central Kalimantan Province to the commonagricultural sectors (agriculture, fisheries and forestry) in 2016 ± 22.1%. GRDP of common agricultural sector in EastKotawaringin District in 2014 ±23.85% with the contribution of the plantation sector ±19.25%. Low contribution offorestry sector to GRDP, it was supposed that the sector is less promising. This research aims to determineeconomic benefits value of secondary forests and lost value in case of forests conversion into oil palm plantations,rubber plantations and coconut plantations. This research conducted in East Kotawaringin District during ± 6 monthswith observation area covers 7 subdistricts through field survey and secondary data. The results showed that totaleconomic value (TEV) of secondary dry forest with large areas ± 20,800 ha ± Rp 769.4 billion per years, TEV ofsecondary swamp forest with large areas ± 12,900 ha ± Rp 453.6 billion per years, TEV of secondary mangroveforests with large areas ± 2,900 ha ± Rp 83.9 billion per yearsKeywords: Keywords: economic valuation, secondary forest, forest conversion, plantation